2022
DOI: 10.1177/09603271221077684
|View full text |Cite
|
Sign up to set email alerts
|

Shenfu Administration Improves Cardiac Fibrosis in Rats With Myocardial Ischemia-Reperfusion Through Adenosine A2a Receptor Activation

Abstract: Objective Shenfu injection (SFI) is commonly used for cardiac dysfunction in China. Adenosine receptors have been reported to exert anti-fibrosis effects. The intent of this study was to evaluate that SFI attenuates cardiac fibrosis through activating of adenosine A2a receptor (A2aR) in rats with myocardial ischemia-reperfusion (MI/R). Methods Sprague Dawley male rats were randomly divided into five groups, nine rats in each group. Injections in all rat groups were carried out prior to reperfusion, and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Inflammatory cells can also stimulate repair pathways, with increasing the content of extracellular matrix in the myocardium, including matrix metalloproteinase-9 (MMP-9) and collagen ( Valiente-Alandi et al, 2018 ). SFI has anti-inflammatory effect, which can reduce the content of inflammatory factors such as tumor necrosis factor-α (TNF-α), interleukin-1𝛽 (IL-1𝛽) and interleukin-6 (IL-6) in serum of rats, and also reduce the expression of fibronectin, collagen I, collagen III and MMP-9 protein ( Ni et al, 2017 ; Guo et al, 2022 ).…”
Section: Pharmacological Activities Of Sfi On Cvdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cells can also stimulate repair pathways, with increasing the content of extracellular matrix in the myocardium, including matrix metalloproteinase-9 (MMP-9) and collagen ( Valiente-Alandi et al, 2018 ). SFI has anti-inflammatory effect, which can reduce the content of inflammatory factors such as tumor necrosis factor-α (TNF-α), interleukin-1𝛽 (IL-1𝛽) and interleukin-6 (IL-6) in serum of rats, and also reduce the expression of fibronectin, collagen I, collagen III and MMP-9 protein ( Ni et al, 2017 ; Guo et al, 2022 ).…”
Section: Pharmacological Activities Of Sfi On Cvdsmentioning
confidence: 99%
“…(IL-1?) and interleukin-6 (IL-6) in serum of rats, and also reduce the expression of fibronectin, collagen I, collagen III and MMP-9 protein (Ni et al, 2017;Guo et al, 2022).…”
Section: Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%
“…Additionally, a study conducted in China in 2022 shed light on the beneficial effects of Shenfu injection (SFI), a commonly employed treatment for cardiac dysfunction in China. The study illustrated that SFI attenuated cardiac fibrosis through the activation of adenosine A2A receptors (A2ARs) in a rat model of myocardial ischemia-reperfusion (MI/R) [48].…”
Section: Adenosine-mediated Effectsmentioning
confidence: 99%
“…The protective role of BGN downregulation is probably due to its involvement as a structural molecule in the assembly of collagen, as well as its action as a signaling molecule in stimulating different cell functions [ 20 , 24 , 25 ]. In fact, previous studies already demonstrated that the adenosine A 2A receptor may contribute to the development of fibrotic damage mainly through the stimulation of collagen production and deposition [ 28 , 29 ], and its modulation might be useful to manage cardiac fibrosis by limiting fibrotic scar deposition in tissue [ 30 ] and also in the heart [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%